2018
DOI: 10.1016/s2352-4642(17)30148-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent resilience to addiction: a social plasticity hypothesis

Abstract: The prevalence of substance use disorders is highest during adolescence; however, many adolescents experience a natural resolution of their substance use by early adulthood, without any formal intervention. Something appears to be unique and adaptive about the adolescent brain. In this Review, we examine the roles of the social environment and neurocognitive development in adolescents' natural resilience to substance use disorders. At present, little is known about the neurocognitive mechanisms that underlie t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 69 publications
3
92
0
6
Order By: Relevance
“…The rates and patterns of adolescent substance use have maintained historical consistency throughout the past several decades. Alcohol continues to be the top substance used by adolescents across the globe (Cousijn et al., ; Feldstein Ewing et al., ). Noted in top U.S. surveys (CDC, ; Johnston et al., ), even though the legal age of purchase and consumption is 21 years, alcohol is highly accessible for American youth, with most accessing alcohol through peers or other individuals (CDC, ).…”
Section: Prevalence Of Adolescent Substance Usementioning
confidence: 99%
“…The rates and patterns of adolescent substance use have maintained historical consistency throughout the past several decades. Alcohol continues to be the top substance used by adolescents across the globe (Cousijn et al., ; Feldstein Ewing et al., ). Noted in top U.S. surveys (CDC, ; Johnston et al., ), even though the legal age of purchase and consumption is 21 years, alcohol is highly accessible for American youth, with most accessing alcohol through peers or other individuals (CDC, ).…”
Section: Prevalence Of Adolescent Substance Usementioning
confidence: 99%
“…To measure the salience of alcohol stimuli for young adult drinkers, who mainly drink in social settings, we used a cue-reactivity task and a behavioral approach bias task with pictures that include this social context, that is, pictures showing people having a beer/soda in a bar, in addition to plain alcohol and soda pictures. Because we expect that embedding the social setting into alcohol cues will increase their incentive value, we expect that social alcohol pictures elicit stronger brain responses than alcoholic pictures without social context in reward-related regions (e.g., VS, vmPFC, ACC), and in brain regions that are known for their role in social processing (e.g., superior temporal sulcus, temporoparietal junction, (dorso)medial prefrontal cortex, ACC) (Amodio & Frith, 2006;Apps, Rushworth, & Chang, 2016;Cousijn, Luijten, & Feldstein Ewing, 2018;Ruff & Fehr, 2014;Witteman et al, 2015). We also expect a larger behavioral approach bias to social compared to non-social alcohol cues, reflected in an approach bias to social alcohol cues.…”
Section: Introductionmentioning
confidence: 99%
“…; Cousijn et al . ). Specifically, during late childhood and early adolescence period, the FHP group continued to have thicker cortices in bilateral precentral regions extending to left caudal MFG, left IFG, bilateral TPJ, and right ITG, possibly suggesting delayed gray matter maturation for age (Paus ).…”
Section: Discussionmentioning
confidence: 97%
“…The process of adolescent neurodevelopment supports several adaptive brain functions responsible for improvement in executive, social and motivated behaviors (Crone & Dahl ; Luciana ; Cousijn, Luijten, & Ewing ). Neuroimaging studies have identified substantial thinning of cortical gray matter regions during adolescence that are marked by both linear and non‐linear patterns (Shaw et al .…”
Section: Introductionmentioning
confidence: 99%